Effects of co-application of tiotropium bromide and traditional Chinese medicine on patients with stable chronic obstructive pulmonary disease: a muilticenter, randomized, controlled trial study - Chen, Ruilin; Ni, Kaiwen; Ji, Conghua; Liu, Zhongda; Yu, Yali; Liu, Gang; Yang, Junchao; Wang, Zhen (Frontiers in Medicine, 2024)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a common, preventable, and treatable disease. Traditional Chinese Medicine (TCM) has shown promising potential in COPD treatment. and we conducted a multi-center RCT to evaluate the effectiveness of TCM-based therapy in stable COPD patients. Methods: In this multicenter, double-blind RCT, a total of 200 patients were supposed to be assigned to either trial or control group randomly. Both groups received Tiotropium (18 μg) from month 0 to month 12. Trial group received additional TCM granules, while control group received a placebo from month 0 to month 6. Symptom assessment, total effective rate, lung function measurements, hospitalization rates, and quality of life were evaluated at month 0, month 6, and month 12. Adverse events were assessed at month 12. Results: Of the initial 105 patients (aged 40-80) who completed the study, 51 were in trial group and 54 were in control group. At month 6, significant differences were observed between two groups in total effective rate (p=0.020), sputum score (p=0.047), changes in FVC% (p=0.047) and FEV1 (p=0.046). At month 12, significant differences were observed in sputum score (p=0.020), FVC (p=0.042), and change in FEV1 (p=0.013). Compared to baseline, they both demonstrated improvements in symptoms, acute exacerbation, lung function, quality of life, and exercise tolerance. Conclusion: TCM treatment effectively improved total effective rate, sputum symptom, FVC%, FEV1, and exhibited prolonged efficacy in improving sputum symptoms and FEV1 in stable COPD patients. Trial registration number: ChiCTR-TRC-13003531, registered on August 29, 2013.